The influence of steel fiber type on the flexural performance of steel fibre reinforced concrete beam - Jazlan, Nurul Amira; Goh, Lyn Dee; Ahmad, Hazrina; Ismail, Ruqayyah; Ahmad Zakwan, Fariz Aswan; Wahid, Norlizan (Faculty of Civil Engineering, 2025)
Concrete is the most widely used structural material due to its excellent workability and high strength. However, ordinary concrete has several drawbacks, including low tensile strength, low ductility and low crack resistance which leads to brittle failure. In this study, hooked end steel fiber of different type and content is used as reinforcements to evaluate the flexural performance of steel fiber reinforced concrete (SFRC) beam. The flexural performance encompasses parameters such as crack pattern, crack width, and deformation behavior under three-point bending. The research methodology involves the preparation and testing of SFRC beams with controlled fiber content of 0.25% and 0.5% and different steel fiber shapes of 3D steel fiber and 4D steel fiber. Fifteen (15) numbers of cube samples with dimension 150 x 150 x 150 mm were tested for its compressive strength and ten (10) beam samples with dimension 100 x 100 x 500 mm were tested for its flexural strength, and their performance were assessed through load-displacement curves, crack pattern observations, and measurement of crack width. The experimental data analyzed to determine the flexural strength, failure modes, and the influence of steel fiber type and content on the overall performance of the SFRC beams shows that the addition of hooked-end 4D steel fiber with 0.5% fiber content improved the flexural performance of SFRC beams when compared to other type of steel fibre reinforced concrete beams. Hooked-end 4D steel fiber with 0.5% fiber content thus approved for use in the fabrication of beams for structural and infrastructural use. Steel fiber in concrete beams proven to improve flexural performance as it offers better control over the crack propagation in a concrete structure.